2015
DOI: 10.7727/wimj.2014.084
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Kidney Disease among Patients Attending a Specialist Diabetes Clinic in Jamaica

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
8
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 14 publications
5
8
3
Order By: Relevance
“…As for risk factors, this study found a significant association between older age group (>50 years), and KD. This is consistent with findings from other studies [6,9,11,12]. It was reported that eGFR will decline gradually with age and at the age >50 years whatever the equations were used; 25% of the diabetics will have eGFR <90 mL/min [17].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As for risk factors, this study found a significant association between older age group (>50 years), and KD. This is consistent with findings from other studies [6,9,11,12]. It was reported that eGFR will decline gradually with age and at the age >50 years whatever the equations were used; 25% of the diabetics will have eGFR <90 mL/min [17].…”
Section: Discussionsupporting
confidence: 91%
“…Our prevalence estimate of KD was lower than 86.3% reported in Jamaica [9] and 82.6% in Kenya [11], but higher than that of 25.3% reported in Brazil [12] and 27.9% in Spain [13]. These differences in KD prevalence might be because of the differences in case difference in creatinine assays and calibration or due to the use of Cockroft-Gault equation for estimation of GFR could also have led to an underestimation of GFR & thus a higher prevalence of KD.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Based on KDIGO (Kidney Disease Improving Global Outcomes) risk categories, 50.8% and 17.4% were at high risk or very high risk of adverse outcomes, respectively. 22 Our study has shown that 69.32% of the chosen specialties (geriatrics, diabetes and endocrinology, haematology, urology, cardiology and vascular surgery) deal with CKD patients.…”
Section: Discussionmentioning
confidence: 82%
“…Among 132 women and men with a mean age of 55.4 years (AE12.9) and a mean duration of diabetes of 16.7 years (AE11.7), 22% had an estimated glomerular filtration rate < 60 ml/min per 1.73 m 2 , while increased urine albumin excretion defined as an albumin-to-creatinine ratio $ 30 mg/g was present in 83%. 2 Overall prevalence of end-stage renal disease (ESRD) in Jamaica also appears to be increasing. Data from the Jamaica arm of the Caribbean Renal Registry shows that the number of persons with CKD and ESRD is increasing, and reported causes are hypertension and diabetes mellitus, with some cases attributed to lupus nephritis and chronic glomerulonephritis.…”
mentioning
confidence: 99%